Daily transactional and transformational leadership and daily employee engagement. Issue 1 (5th October 2013) - Breevaart, Kimberley; Bakker, Arnold; Hetland, Jørn; Demerouti, Evangelia; Olsen, Olav K.; Espevik, Roar
<x xml:space="preserve">Abstract</x> This diary study adds to the leadership literature by examining the daily influence of transformational leadership, contingent reward, and active management‐by‐exception (MBE active) on followers' daily work engagement. We compare the unique contribution of these leadership behaviours and focus on the work environment to examine how these leadership behaviours influence followers' daily work engagement. While travelling by sail ship, 61 naval cadets filled out a diary questionnaire for 34 days. Multilevel regression analyses revealed that, after controlling for followers' work engagement the previous day, cadets were more engaged on days that their leader showed more transformational leadership and provided contingent reward. MBE active was unrelated to followers' work engagement. As predicted, transformational leadership and contingent reward contributed to a more favourable work environment (more autonomy and support), while MBE active resulted in a less favourable work environment (less autonomy) for the cadets. This study highlights the importance of daily leadership for followers' daily work engagement. Practitioner points Leaders' daily behaviour influences followers' daily work engagement. Leaders' daily behaviour shapes the daily work environment.